ความรุนแรงในสถานที่ทำงาน: ศึกษากรณีเจ้าหน้าที่และบุคลากรของโรงพยาบาลตำรวจ - แสงสวัสดิ์, รมิดา (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: To examine the effects, forms and reasons of the violence in the workplace and to find guidelines for preventing and solving the violence in the workplace for the officers and staff of Police General Hospital. METHODS: It was a mixed method research. The samples and main informants were 204 officers and staff of the Hospital. The research instruments were online questionnaires, and information filling forms questionnaires for quantitative studies and as well as interviews schedule for qualitative studies. RESULTS: The most common form of violence was verbal violence. The most common verbal and physical violence users in the workplace were associates within the same organization. In most cases, the violent incident caused no injury and the persons can continue their work as usual. However, there were mental and emotional effects in some cases, and people might choose to stop working, to move to other organizations, or to resign. Social environment factors were the most significant factors which created violence. CONCLUSIONS: The prevention of and solution to this problem included training projects to create awareness of the disadvantages and effects of the problem. Moreover, the management was suggested to be ready to deal with violence in the workplace through suitable approaches.